SHEDDING LIGHT ON THE TAXONOMIC DIVERSITY OF THE SOUTH AMERICAN MIOCENE CAIMANS: THE STATUS OF MELANOSUCHUS FISHERI (CROCODYLIA, ALLIGATOROIDEA) (Ameghiniana, 2017)
Melanosuchus niger Spix is distributed throughout the Amazon River basin today. The extinct Melanosuchus fisheri Medina from the late Miocene of Venezuela was erected based on two almost complete, but heavily deformed skulls (the holotype MCNC 243 and the referred specimen MCZ 4336), which show morphological differences from each other. The comparison indicates that only the holotype can be referred to Melanosuchus Gray. We propose MCZ 4336 is a representative of the caimanine Globidentosuchus brachyrostris Scheyer, Aguilera, Delfino, Fortier, Carlini, Sánchez, Carrillo-Briceño, Quiroz and Sánchez-Villagra. Although the taxonomy of M. fisheri is taken into question herein, the classification of the holotype still sustains the hypothesis that the genus is registered in South America since the late Miocene.